Acutely deteriorated extravascular volume overload during peripheral blood stem cell mobilization in POEMS syndrome: A case series with cytokine analysis. Issue 2 (April 2016) - Muto, Tomoya; Ohwada, Chikako; Sawai, Setsu; Beppu, Minako; Tsukamoto, Shokichi; Takeda, Yusuke; Mimura, Naoya; Takeuchi, Masahiro; Sakaida, Emiko; Sogawa, Kazuyuki; Misawa, Sonoko; Shimizu, Naomi; et al.
Abstract: We describe two cases of polyneuropathy, organomegaly, endocrinopathy, monoclonal protein, and skin changes (POEMS) syndrome patients with deteriorated extravascular volume overload without increased levels of vascular endothelial growth factor after the administration of cyclophosphamide + granulocyte colony-stimulating factor for stem cell mobilization. We then measured the serum levels of 27 cytokines from these cases using a multiplex suspension array system. The analysis revealed the changes of cytokine profiles before cyclophosphamide + granulocyte colony-stimulating factor and after the development of capillary leak symptoms in both cases. This may improve our current level of understanding of the pathogenesis of POEMS syndrome not driven by vascular endothelial growth factor.